Linking the approaches of epidemiology and mathematical modelling for the evaluation of public health strategies - (:unkn) unknown (My University, 2023)
Epidemiology and mathematical modelling are two types of tools for the quantification of health risks. These two approaches especially differ by their relationship to the data, the level of confidence in the evidence they produce, and the space-time horizons for the estimates produced. This manuscript presents my recent and forthcoming research work, which articulates epidemiological and modelling approaches for the evaluation of public health prevention strategies.My recent research has mostly focused on the evaluation of infectious disease prevention strategies in Africa. Part of this work has evaluated the behavioural and socio-economic effects of HIV prevention programmes in sub-Saharan Africa. In particular, this work has led to a better understanding of the temporal and spatial dynamics of socio-economic inequalities in the uptake of HIV prevention in the region. Another part of my work focused on the epidemiology and modelling of yellow fever in Africa, together with the evaluation of vaccination strategies. By developing a model integrating various kinds of data (demographic, environmental, serological, vaccine-related data), I was able to estimate the burden of disease across the African region endemic or at risk for yellow fever, and also to evaluate the impact of past and future vaccination strategies. Finally, a third part of this work, currently under development, focuses on the circulation of infectious agents in health care settings, in particular hepatitis C virus and SARS-CoV-2 within Egyptian hospitals. This research axis aims to evaluate and model the circulation of these pathogens within hospitals, or at the interface between hospitals and the community, in order to propose and evaluate different control strategies.Beyond the prolongation of my recent work, I plan to extend this articulation of approaches to non-infectious conditions, particularly in relation with work-related diseases and with the health co-benefits of climate chan
Keywords: African Research